2010
DOI: 10.1371/journal.pone.0011222
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Ionizing Radiation Promote Tumor Growth and Metastasis by Enhancing Angiogenesis

Abstract: Radiotherapy is a widely used treatment option in cancer. However, recent evidence suggests that doses of ionizing radiation (IR) delivered inside the tumor target volume, during fractionated radiotherapy, can promote tumor invasion and metastasis. Furthermore, the tissues that surround the tumor area are also exposed to low doses of IR that are lower than those delivered inside the tumor mass, because external radiotherapy is delivered to the tumor through multiple radiation beams, in order to prevent damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 21 publications
(27 reference statements)
6
104
1
Order By: Relevance
“…Radiation-induced up-regulation of integrin- (Wild-Bode et al, 2001; Nalla et al, 2010; Canazza et al, 2011; Rieken et al, 2011), VEGF- (Sofia Vala et al, 2010; Badiga et al, 2011; Kil et al, 2012), EGF- (Kargiotis et al, 2008; Pickhard et al, 2011) or/and TGFbeta signaling (Canazza et al, 2011; Zhou et al, 2011) has been proposed to promote tumor cell migration. Downstream ion transport processes have been reported for glioblastoma cells (Steinle et al, 2011).…”
Section: Ion Transports and Radioresistancementioning
confidence: 99%
“…Radiation-induced up-regulation of integrin- (Wild-Bode et al, 2001; Nalla et al, 2010; Canazza et al, 2011; Rieken et al, 2011), VEGF- (Sofia Vala et al, 2010; Badiga et al, 2011; Kil et al, 2012), EGF- (Kargiotis et al, 2008; Pickhard et al, 2011) or/and TGFbeta signaling (Canazza et al, 2011; Zhou et al, 2011) has been proposed to promote tumor cell migration. Downstream ion transport processes have been reported for glioblastoma cells (Steinle et al, 2011).…”
Section: Ion Transports and Radioresistancementioning
confidence: 99%
“…Indeed breast cancer molecular subtypes defined by transcriptomic profiling can also be characterized by methylome profiling (52), suggesting that the two may go hand-in-hand. Identical hypermethylated genes occur in histologically normal ducts that are adjacent to pre-invasive and invasive lesions, suggesting a common loco-regional etiology mediated by methylation (9,53,54). …”
Section: Discussionmentioning
confidence: 99%
“…It is generally realized that the effects of high-and low-dose radiotherapy vary. Sofia Vala et al [38] found that low doses of radiotherapy (0.5 Gy) induced rapid phosphorylation of several endothelial cell proteins, including VEGF receptor (VEGFR)-2 and induced VEGF production in hypoxia mimicking conditions. This effect may explain why they found that low-dose irradiation actually enhanced angiogenesis and endothelial cell migration.…”
Section: Angiogenesis Inhibition In Combination With Radiotherapymentioning
confidence: 99%